2000
DOI: 10.1007/s002320010001
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations and Fractal Noise in Biological Membranes

Abstract: Our understanding of cell structure and function derives from applications of a variety of physical and life science disciplines, methods and models to an important physiological process, namely, the exchange and transport of ions and molecules across biological membranes. We know that ion transport through membranes arises from a diversity of interrelated and interactive physical and chemical phenomena over a wide range of spatial and temporal scales. Among these phenomena common to all cellular structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 32 publications
2
37
0
1
Order By: Relevance
“…Fractality has been invoked in the Weld of membrane biophysics in connection with a number of phenomena ranging from the geometry of self-aggregated vesicles (Lahiri et al, 1998), the folding of the membrane in 3D space (Paumgartner et al, 1981), the kinetics of channel conductance (Hoop and Peng, 2000), experimentally observed lipid domain topography (Miller et al, 1986) and its simulation (Fogedby et al, 1987), and lateral surface defects or diVusion (Nonnenmacher, 1989;Pink et al, 1991). In connection with lipid domains the focus has traditionally been on the determination of percolation thresholds of bilayer domains at thermotropic phase transition points through Xuorescence recovery after photobleaching (FRAP) experiments (Almeida and Vaz, 1995).…”
Section: Domain Size and Fractal Dimensionmentioning
confidence: 99%
“…Fractality has been invoked in the Weld of membrane biophysics in connection with a number of phenomena ranging from the geometry of self-aggregated vesicles (Lahiri et al, 1998), the folding of the membrane in 3D space (Paumgartner et al, 1981), the kinetics of channel conductance (Hoop and Peng, 2000), experimentally observed lipid domain topography (Miller et al, 1986) and its simulation (Fogedby et al, 1987), and lateral surface defects or diVusion (Nonnenmacher, 1989;Pink et al, 1991). In connection with lipid domains the focus has traditionally been on the determination of percolation thresholds of bilayer domains at thermotropic phase transition points through Xuorescence recovery after photobleaching (FRAP) experiments (Almeida and Vaz, 1995).…”
Section: Domain Size and Fractal Dimensionmentioning
confidence: 99%
“…hydrophobic or van der Waals interactions between membrane lipids, may be programmed by incoming synaptic signals that modulate the shape of a spatially extended, fractal lipid lattice or microdomain (Bieberich, 2000a). Recently, it has been found that biological membranes exhibit requisite characteristics of fractal geometry with respect to curvature, shape, and internal molecular organization (Hoop and Peng, 2000;Rabouille et al, 1992;Sugar et al, 2001). Alternatively, microtubules or other filaments of the cytoskeleton may also form a lattice structure that can be shaped into a fractal.…”
Section: Conclusion: Rfnns and Consciousnessmentioning
confidence: 99%
“…Many important physiological membrane functions [such as enzymatic activities, membrane permeability, hormonal response, etc. (18)(19)(20)] are modulated by physico-chemical properties of the lipid bilayer. For example, many physiological processes involve changes in the amount of water bound to lipid bilayer (20), which affects, in particular, the membrane interfacial polarity.…”
mentioning
confidence: 99%